Neonatal and pediatric intensive care units: accounts on the practice of occupational therapists - Menegat, Danusa (2022)
Objective: to characterize the practices of occupational therapists in neonatal and pediatric intensive care units. Methods: a quantitative-qualitative study, carried out in 2017, with data collection through an online questionnaire with occupational therapists who worked with intensive care. The interpretation was performed using simple descriptive statistics and thematic analysis. Results: 15 occupational therapists participated, with postgraduate degrees; female; aged 24 to 60 years; with a mean age of 28 years; the average working time in a hospital and intensive care environment exceeded four years. Four categories emerged: Actions by the Occupational Therapist in the ICU; Resources and techniques used by the Occupational Therapist in the ICU; Training of Occupational Therapists to work in an ICU; and Occupational Therapist Perceptions related to the ICU routine and team recognition. The actions focused on physical and cognitive interventions and guidance to family members and patients. Conclusion: It is necessary to expand and deepen the studies on the work developed by occupational therapists in intensive care units, aiming at the creation and establishment of indicators that favor professional qualification and consolidation.